Characterization of a new partitivirus strain in Verticillium dahliae provides further evidence of the spread of the highly virulent defoliating pathotype through new introductions - CAÑIZARES, Mari Carmen; PÉREZ-ARTÉS, Encarnación; GARCÍA-PEDRAJAS, Nicolás; GARCÍA-PEDRAJAS, María (Phytopathologia Mediterranea, 2015)
The soilborne pathogen Verticillium dahliae, causal agent of Verticillium wilt, has a worldwide distribution and many hosts of agronomic value. The worldwide spread of a highly virulent defoliating (D) pathotype has greatly increased the threat posed by V. dahliae in olive trees. For effective disease management, it is important to know if the D pathotype is spreading long distances from contaminated material, or if D pathotype isolates may have originated locally from native V. dahliae populations several times. We identified a double-stranded RNA mycovirus in an olive D pathotype isolate from Turkey. Sequencing and phylogenetic analysis clustered the virus with members of the family Partitiviridae. The virus was most similar to a partitivirus previously identified in a V. dahliae isolate from cotton in China (VdPV1), with sequence identities of 94% and 91% at the nucleotide level for RNA1 and RNA2, respectively. The virus therefore corresponded to a strain of the established species, and we designated it VdPV1-ol (VdPV1 from olive). The identification of the same viral species in these two fungal isolates from geographically distant origins provides evidence of their relationships, supporting the hypothesis of long-distance movement of V. dahliae isolates.